2022
DOI: 10.1002/vms3.833
|View full text |Cite
|
Sign up to set email alerts
|

Effects of riboflavin on boar sperm motility, sperm quality, enzyme activity and antioxidant status during cryopreservation

Abstract: Objectives This study was conducted to evaluate the effect of adding riboflavin to boar sperm freezing extender on the challenge of cryopreservation. Methods Different concentrations (0, 5, 10, 15, 20 or 25 μM) of riboflavin were added to the freezing extender. Spermatozoa motility, membrane integrity, acrosomal integrity, mitochondrial membrane potential and enzyme activities were analysed once 10 min after thawing. Q‐PCR was used to detect the mRNA expression of Caspase3, Bcl‐2 and Bax. Results The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…During cryopreservation, an increase in free radicals leads to oxidative stress, which leads to structural and functional changes and finally apoptosis. Myo-inositol improves sperm quality, reduces ROS production, protects acrosome integrity and mitochondrial function, protects against cryodamage, and reduces apoptosis [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…During cryopreservation, an increase in free radicals leads to oxidative stress, which leads to structural and functional changes and finally apoptosis. Myo-inositol improves sperm quality, reduces ROS production, protects acrosome integrity and mitochondrial function, protects against cryodamage, and reduces apoptosis [ 40 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sperm are produced in supraphysiological doses of ROS during cryopreservation and thawing, which leads to reduced sperm motility and viability, and increases the risk of DNA damage (Khosravizadeh et al, 2022). Numerous studies in recent years have shown that the exogenous antioxidants, including butylated hydroxytoluene, reduced glutathione (de Andrade et al, 2023), riboflavin (Dong et al, 2022), melatonin (Pezo et al, 2021), astaxanthin (Guo et al, 2021), rutin (Xu et al, 2020), resveratrol (Zhu, Li, et al, 2019) and alpha lipoic acid (Shen et al, 2016) have been applied to extenders to minimize the level of oxidative stress caused by ROS to boar sperm during cryopreservation.…”
mentioning
confidence: 99%